Russia's Federal Relations : Putin's Reforms and Management of the Regions. - Chebankova, Elena (BASEES/Routledge Series on Russian and East European Studies, 63., 2009)
Examines the origins, underlying foundations, and dynamics of the federal reforms conducted by President Putin throughout the eight years of his presidency. This book discusses the intentions of the federal centre and the very different results that have turned out.